Translation and cross-cultural adaptation of the Brazilian version of BREAST-Q©: breast reconstruction expectations module - Oliveira,Iara Gama Esteves de (2022)
SUMMARY OBJECTIVE: This study aimed to translate the BREAST-Q© — Breast Reconstruction Expectations Module (preoperative) 2.0 into Portuguese and adapt it to the Brazilian cultural context. METHODS: Authorization for translation and cross-cultural adaptation of the questionnaire was obtained from the holders of the instrument's distribution rights. The questionnaire was translated and retro-translated. For cultural adaptation, the instrument was applied to 40 patients who had breast reconstruction surgery scheduled. Cronbach's alpha was used to assess the internal consistency. RESULTS: The mean age of the patients was 53.5 years, and the majority (72.5%) was undergoing reconstruction with implants. Good and excellent internal consistencies were observed for the Coping and Appearance expectations scales (Cronbach's alpha values of 0.878 and 0.909, respectively). For the Pain scale, the internal consistency was moderate (0.738), and it was acceptable (0.587) for the Medical team. CONCLUSION: The BREAST-Q© — Breast Reconstruction Expectations Module (preoperative) 2.0 was successfully translated and adapted to the Brazilian context.